Trade fair activity and sustainable urban development, through the lens of Thessaloniki International Fair - Dimitris Kourkouridis; Yannis Frangopoulos; Nikos Kapitsinis (International Journal of Urban Sustainable Development)
This paper explores a new perspective on trade fairs, examining their expected impact on the sustainable development of the host city. To study this impact, the paper examines the annual fair of Thessaloniki, Greece, which has a long history and strong connection with the city. Methodologically, mix research method is used, combining quantitative and qualitative methods. The findings challenge the focus of trade fairs’ benefits in terms of sustainability on the economic aspect. Thessaloniki citizens believe that the fair contributes positively to sustainable urban development, possibly due to their emotional attachment with it and its crucial economic benefits. Stakeholder interviews, however, reveal concerns. Some attribute limitations to outdated fair infrastructure, claiming that a planned redevelopment could address sustainability issues. Others, more critical of the fair, argue that achieving truly balanced development is difficult within the existing mode of socio-economic organisation.